2022
DOI: 10.1155/2022/5491621
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lifeboat Embarkation Efficiency for Cruise Passengers under Multiple Scenarios

Abstract: Lifeboats are important equipment to ensure the safety of passengers when a serious accident occurs in the ship. Higher efficiency of lifeboat embarkation is beneficial to improving passenger survival. This study divides lifeboat embarkation into queuing and seat selection stages and studies the embarkation process of cruise passengers. According to the characteristics of two stages of the embarkation process, transfer rules of queue and activity rules of the passenger are proposed. Combined with the rules, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Similarly, few researchers [12][13] have also utilized decision trees, like CART, Random Forest, Boosted Trees, or ANN, to model the safety of vehicles and pedestrians on road. Hu and Cai (2022) [14] reported that the logistic model is first applied for relationship explanation, and then the machine learning classifiers like ANN or Fuzzy are applied for prediction modeling. Tamakloe et al (2022) [15] opined that logistic regression helps in identifying the individual effect of factors affecting crash severity.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, few researchers [12][13] have also utilized decision trees, like CART, Random Forest, Boosted Trees, or ANN, to model the safety of vehicles and pedestrians on road. Hu and Cai (2022) [14] reported that the logistic model is first applied for relationship explanation, and then the machine learning classifiers like ANN or Fuzzy are applied for prediction modeling. Tamakloe et al (2022) [15] opined that logistic regression helps in identifying the individual effect of factors affecting crash severity.…”
Section: Resultsmentioning
confidence: 99%